Kecenderungan Perilaku Pengambilan Resiko dengan Minat Berwirausaha - Triawan Triawan; Sumaryono Sumaryono (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2008)
This current research investigated the possible correlation between risk-taking behavior tendency and entrepreneurship intention. Seventy (70) University students in their senior years were assessed using risk-taking behavior scale and entrepreneurship intention scale. Using The result shows that the tendency in high-risk taking behavior is strongly correlated with entrepreneurship intention, which is the higher the tendency for risk-taking behavior, the stronger its intention for entrepreneurship.